THE INTERNATIONAL LEGAL RESPONSIBILITY OF A HOST STATE FOR THE DESTRUCTION OF FOREIGN INVESTMENT LOCATED IN ITS TERRITORY ICSID: Award, Individual Opinion and Declaration in American Manufacturing & Trading Incorporated v Republic of Zaire 36 ILM 1531 (19 - John Baloro (Obiter, 2023)
In recent years on the international stage, it has become very common practice for developing countries, eager to attract the flow of private foreign direct investment capital into their economies, to conclude Bilateral Investment Treaties (BITs) with the developed capital-exporting countries. Recent studies have estimated that, since the 1980s, well in excess of 900 such treaties have been concluded. This note examines the international rights and duties of the contracting parties to one such treaty which was concluded between the United States of America and the then Republic of Zaire, now known as the Democratic Republic of Zaire. It discusses the nature of the international legal responsibility which Zaire as a host state owes foreign nationals and their corporations which invest in her territory under both customary and conventional international law. It is firmly concluded that host states such as the Republic of Zaire clearly act in breach of their international legal responsibilities when they fail to put in place the necessary measures and environment for the protection and security of foreign nationals, their investments, and properties located in the territory of the host state. The note further states that in this area of public inter-national law, it is generally agreed that there is an international minimum standard which applies and a host state cannot rely on its own municipal law and practice which falls below the standard of international law.